How FTAI and FTET impact reproductive efficiency of Brazilian dairy herds - Rodrigues, Carlos Alberto; Ferreira, Roberta Machado; Vieira, Lais Mendes; Ranieri, Andressa L. [UNESP]; Silva, Péricles R.L.; Baruselli, Pietro Sampaio (My University, 2011)
Background: Throughout dairy cows evolution, milk production was always the key point to select the superior animal. Currently, several evidences has shown that high milk production have intensively contributed to the decline of dairy cattle fertility. Beyond milk production, dairy cows have their reproductive performance impaired by another factors, heat stress and repeat-breeding. Methods like fixed time artificial insemination and embryo transfer were developed to minimize the effects of these factors, and improve dairy herds profitability. This review aims to show some key-point experiments conducted to improve the efficiency of the self-appointed protocols for artificial insemination and embryo transfer in Brazil, overcoming several reproductive problems. Our goal is to develop cheap and easy self-appointed programs that facilitate animal handling and maximize their reproductive outcomes all over the year. Review: Failure in estrus detection is the mainly limiting factor for the use of artificial insemination in high-production dairy herd. An excellent alternative to overcome the need of estrus detection is fixed time artificial insemination. Many protocols with and without the use of estradiol have been developed to that end. Among the protocols for fixed time artificial insemination without estradiol, DoubleOvsynch has been extensively used recently in American dairy herds. In Brazil, similar pregnancy rate was obtained compared to progesterone-estradiol based protocols for fixed time artificial insemination. Particularities of progesterone-estradiol based protocols as (1) new progesterone device or devices previously used for eight days; (2) different doses of eCG; and (3) the use of estradiol cypionate for fixed time artificial insemination have been studied in Brazil. The use of self-appointed artificial insemination also enabled the reduction of the interval calving-conception compared to cows inseminated following the standing estrus. Regarding the low fertility of repeat breeders and the effect of heat stress at early pregnancy, other methods like embryo transfer became important tools to enhance reproductive efficiency of Brazilian dairy herds. Protocols were also developed to allow fixed time embryo transfer, eliminating the need of estrus detection and improving the reproductive efficiency of lactating recipients. As well as described for fixed time artificial insemination treatments, there is a large variety of hormone combination for fixed time embryo transfer (with and without estradiol). An experiment conducted in Brazil demonstrated that protocols for fixed time embryo transfer without estradiol can be as good as with estradiol to synchronize high-producing Holstein recipients, essentially during summer. Particularities related to embryos cryopreservation, synchronization of the estrus cycle of donors and recipients and the site of embryo release into the uterine horn were also investigated. Greater conception rates were achieved when fresh embryos were transferred compared to frozen-thawed ones. Also, the tight synchronization between donor and recipient (same day of estrus) resulted more pregnancies than when recipients were one day later or in advantage in relation to donors. Moreover, the site of embryo release into the uterine horn (ipsilateral to the corpus luteum) had no effect on pregnancy rates after in vivo produced embryo transfer. Conclusion: Both fixed time artificial insemination and fixed time embryo transfer are important tools to improve reproductive efficiency of high-producing dairy cows. These biotechnologies help bypassing some of the greatest challenges of dairy cattle reproduction: the difficulties of estrus detection, and the low fertility associated to heat stress and repeat breeding.
Keywords: FTAI; FTET; Heat stress; Repeat breeders; Reproductive efficiency; Animalia; Bos